Systolic pulmonary artery pressure assessed during routine exercise Doppler echocardiography: insights of a real-world setting in patients with elevated pulmonary pressures - Korff, Susanne; Uhlmann, Lorenz; Aurich, Matthias; Greiner, Sebastian; Hirschberg, Kristóf; Katus, Hugo; Mereles, Derliz (The international journal of cardiovascular imaging, 2018)
Pulmonary hypertension is a marker of disease severity. Exercise Doppler echocardiography (EDE) has proven to be feasible and reliable to assess pulmonary pressure. Increase in systolic pulmonary artery pressure (sPAP) has diagnostic and prognostic value in controlled studies. However, its value when assessed during routine examination in patients with cardiopulmonary diseases and resting sPAP > 35 mmHg is not clearly defined. Clinical documentation and offline reevaluation of digitally stored EDE examinations of patients with appropriate clinical indications for EDE were analyzed.